2018
DOI: 10.1111/eos.12534
|View full text |Cite
|
Sign up to set email alerts
|

In‐vivo compatibility between pacemakers and dental equipment

Abstract: In-vitro studies suggest that electromagnetic interference can occur under specific conditions involving proximity between electronic dental equipment and pacemakers. At present, in-vivo investigations to verify the effect of using electronic dental equipment in clinical conditions on patients with pacemakers are scarce. This study aimed to evaluate, in vivo, the effect of three commonly used electronic dental instruments - ultrasonic dental scaler, electric pulp tester, and electronic apex locator - on patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…No interference of dental electrical devices was found affecting the function of CIEDs in four clinical studies 21–25 . Three in vivo studies found background noise and electrocardiogram noise while using a gutta‐percha heating device, ultrasonic dental scaler, EPT, and EAL at a preset sensitivity 24–26 …”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…No interference of dental electrical devices was found affecting the function of CIEDs in four clinical studies 21–25 . Three in vivo studies found background noise and electrocardiogram noise while using a gutta‐percha heating device, ultrasonic dental scaler, EPT, and EAL at a preset sensitivity 24–26 …”
Section: Resultsmentioning
confidence: 97%
“…Among these 18 selected studies, 12 were in vitro and six were in vivo studies. Table 1 summarizes the details and results of the in vitro studies, 7,10–20 while the main characteristics of the in vivo studies are shown in Table 2 21–26 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations